Diagnostic phrasing is independently correlated with the decision to treat for graft‐versus‐host disease: retrospective review of colon biopsies with rare apoptosis. Issue 5 (22nd July 2016) - Rowan, Daniel J; Hartley, Christopher P; Carrillo‐Polanco, Luis F; Oshima, Kiyoko; Hagen, Catherine E
Abstract : Aims: The risks of immunosuppression and the non‐specific nature of rare crypt apoptosis has led to debate over the lower threshold for histological diagnosis of colonic graft‐versus‐host disease (GVHD). A recent study proposed the diagnostic category of indeterminate for GVHD (iGVHD) for cases with six or fewer apoptotic bodies per 10 crypts. Our aim was to assess colon biopsies with iGVHD histology to determine whether the diagnosis was retrospectively predictive of the decision to treat, and to correlate these findings with endoscopic and clinical findings. Methods and results: A retrospective search was performed for colonic biopsies taken to evaluate for GVHD from 2008 to 2014. Biopsies were blindly reviewed for the maximum number of apoptotic bodies per 10 contiguous crypts, evidence of crypt dropout, and ulceration. Clinical information was collected through chart review. One hundred and twenty‐two biopsies from 84 transplant patients were included. Forty‐seven cases met the histological criteria for iGVHD. Patients with an original diagnosis of iGVHD were more likely to be managed conservatively than those with a diagnosis of grade 1 GVHD (25% versus 0%). Eight symptomatic patients reclassified as iGVHD had resolution of symptoms without increased immunosuppression. A clinicopathologically similar group of 10 patients with iGVHD histology, normal or subtle endoscopic findings and no evidence of GVHD at other organ sites were treated with increased immunosuppression. On multivariate analysis, the original diagnostic category was the most significant predictor of the decision to treat. Conclusion: The use of the diagnostic category iGVHD alerts clinicians to the presence of minimal crypt apoptosis, and allows treatment based on clinical judgement.